Reading and writing comprehension in the mother tongue in the Romanian national assessment – objectives, tests, results - Szanto, Biborka (Technium Social Sciences Journal, 2020)
In Romania the basic competencies (reading and writing in the student’s mother tongue and in Romanian language in the case of students studying in minority schools, mathematical literacy) of students at the end of the 2nd and 4th grade of primary education are assessed starting with the school year 2013/2014. The paper analyses the tests of the national assessment designed and applied for measuring reading and writing skills in the mother tongue (in Hungarian language). The paper concludes that the tests are not carefully designed in order the measure the most important skills and abilities at the end of the 2nd and 4th grade. The study analyses the achievement in reading and writing of 2nd and 4th grade students’ attending schools teaching in Hungarian. The analysis fills a gap, because the detailed qualitative analyses of the results of elementary school students whose learning language is Hungarian, is missing from the reports presenting the results of the national assessment. Based on the analyses of the objectives, tests and results of the national assessment for reading and writing in Hungarian, the paper formulates the questions that arise regarding the necessity of this measurement.